Network Congestion Aware Multiobjective Task Scheduling in Heterogeneous Fog Environments - TOPCUOĞLU, HALUK RAHMİ (My University, 2023)
Task scheduling on fog environments surges new challenges compared to scheduling on conventional cloud computing. Various levels of heterogeneity and dynamism cause task scheduling problem is more challenging for fog computing. In this study, we present a multiobjective task scheduling model with a total of five objectives and propose a multiobjective multirank (MOMRank) scheduling algorithm for fog computing. The performance of the proposed strategy is assessed with well-known multiobjective metaheuristics [the nondominated sorting genetic algorithm II (NSGA-II) and the Strength Pareto Evolutionary Algorithm 2 (SPEA2)] and a widely used algorithm from the literature, the multiobjective heterogeneous earliest finish time (MOHEFT) algorithm using three common multiobjective metrics. Additionally, we incorporate two task clustering mechanisms to the algorithms in order to improve data transmissions on interconnection networks. Results of empirical evaluations given in performance profiles over all problem instances validate significance of both our algorithm and the integrated extensions for diminishing data transfer costs.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Bilgi Güvenliği ve Güvenilirliği; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Computer Sciences; Information Security and Reliability; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, BİLGİ SİSTEMLERİ; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; ENGINEERING; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, INFORMATION SYSTEMS; ENGINEERING, ELECTRICAL & ELECTRONIC; Fizik Bilimleri; Bilgi sistemi; Bilgisayar Bilimi Uygulamaları; Elektrik ve Elektronik Mühendisliği; Control and Systems Engineering; Physical Sciences; Information Systems; Computer Science Applications; Electrical and Electronic Engineering; Cloud computing; Computational modeling; Costs; Edge computing; Fog computing; Job shop scheduling; metaheuristic techniques; multiobjective optimization; Resource management; Task analysis; task scheduling; workflows